2021
DOI: 10.3390/life11111192
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Systems for Translational Regulation of Synthetic mRNAs in Mammalian Cells

Abstract: Synthetic mRNAs, which are produced by in vitro transcription, have been recently attracting attention because they can express any transgenes without the risk of insertional mutagenesis. Although current synthetic mRNA medicine is not designed for spatiotemporal or cell-selective regulation, many preclinical studies have developed the systems for the translational regulation of synthetic mRNAs. Such translational regulation systems will cope with high efficacy and low adverse effects by producing the appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
(226 reference statements)
0
3
0
Order By: Relevance
“…Previous works demonstrated that MCP form dimer on the MS2 aptamer. This protein‐aptamer complex can physically hinder the ribosome to repress translation [29,30] . Figure S5 shows that the MCP‐ALP switch with D‐3 treatment induced substantial loss of viability of HEK293 cells, while co‐transfection of MCP mRNA resulted in nearly no loss of viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works demonstrated that MCP form dimer on the MS2 aptamer. This protein‐aptamer complex can physically hinder the ribosome to repress translation [29,30] . Figure S5 shows that the MCP‐ALP switch with D‐3 treatment induced substantial loss of viability of HEK293 cells, while co‐transfection of MCP mRNA resulted in nearly no loss of viability.…”
Section: Resultsmentioning
confidence: 99%
“…This protein-aptamer complex can physically hinder the ribosome to repress translation. [29,30] Figure S5 shows that the MCP-ALP switch with D-3 treatment induced substantial loss of viability of HEK293 cells, while co-transfection of MCP mRNA resulted in nearly no loss of viability. Notably, the MCP-Bim switch failed in completely eliminating the HEK293 cells and could not maintain cell viability upon co-transfection of MCP mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike DNAbased drugs, mRNA transcripts have a relatively high transfection efficiency and low toxicity because they do not need to enter the nucleus [71]. In addition, mRNAs do not cause insertional mutagenesis [72,73]. A BNT162b2 mRNA vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) did not induce immune-related adverse events in patients with NSCLCs [74].…”
Section: Mrna Vaccines As Anti-cancer Therapeuticsmentioning
confidence: 99%
“…However, for spatiotemporal and cell-specific control, novel methods distinct from DNA transfection are required. Nakanishi reviews protein-based translational regulatory systems for synthetic mRNAs in mammalian cells [ 6 ]. It is noteworthy that the synthetic mRNAs can express both effector proteins and regulatory proteins, allowing for the construction of multilayered genetic circuits composed entirely of mRNAs.…”
Section: Protein-based Regulatory Systemsmentioning
confidence: 99%